1980
DOI: 10.1182/blood.v56.4.640.640
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom chromosomal aberrations in chronic lymphocytic leukemia revealed by polyclonal B-cell-mitogen stimulation

Abstract: Peripheral blood lymphocytes from 11 patients with chronic lymphocytic leukemia were stimulated by Epstein-Barr virus (EBV), lipopolysaccharide from Escherichia (LPS), and phytohemagglutinin (PHA). Chromosome analysis with the Q-banding technique after 5 days incubation revealed an extra chromosome 12 in 5 of the patients and a translocation between chromosome 11 and chromosome 14 in 1. Two patients had a deletion of chromosome 6, and only 3 patients had a normal karyotype. In most patients, the abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
7

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(37 citation statements)
references
References 31 publications
2
28
0
7
Order By: Relevance
“…Numerical or structural chromosomal 12 abnormalities are often observed in B-cell chronic lymphocytic proliferations and are considered to be of prognostic value (Gahrton et al, 1980;Knuutila et a]. , 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Numerical or structural chromosomal 12 abnormalities are often observed in B-cell chronic lymphocytic proliferations and are considered to be of prognostic value (Gahrton et al, 1980;Knuutila et a]. , 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of B-cell mitogens (Robert et al, 1978) into cytogenetic techniques has made it possible to karyotype the lymphocytes in Kcell chronic lymphocytic leukemia (B-CLL) (Autio et al, 1979;Gahrton et al, 1980) and to define the cytogenetic abnormalities in this disease. Initial studies have shown that B-CLL is a cytogenetically heterogeneous disease, although several recurring abnormalities have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, these cultures aimed at obtaining metaphases from peripheral T-cells in order to verify the constitutional karyotype of the patient and, indeed, the majority of the metaphases were normal. The cytogenetic abnormalities trisomy 12 and t( 14; 18) (q32;q21) have been specifically associated with CLL, lymphocytic lymphomas and follicular lymphomas (9,10). Immunologically, CLL and lymphocytic lymphoma are characterized by moderate expression of SmIg and positivity for T1 antigen (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…In lymphoproliferative disorders, the 14q + is the most commonly reported abnormality: it originates from various translocations, some of them showing specificity like the t(8;14)(q22;q32) in Burkitt lymphomas and ALL-L3 (7, 8) and the t( 14; 18)(q32;q21) in follicular lymphomas (9). Trisomy of chromosome 12 is frequently found in CLL and in small cell lymphocytic lymphomas (9,10). Until recently, for the immunological classification of lymphoproliferative disorders, traditional cell markers were used, such as surface membrane and cytoplasmic immunoglobulin (Ig) and the receptor for sheep red blood cells.…”
mentioning
confidence: 99%